The functional role of phonemes and morphemes in meaning construction (The International Journal for Scientific Research, 2026)
This research addresses the functional role of the phoneme and morpheme in constructing meaning within the Arabic linguistic system. The research aims to explore the mechanisms through which these minimal linguistic units contribute to shaping semantics and guiding communicative intentions, with a focus on the overlapping area known as the "morphophoneme." The study adopts a descriptive-analytical approach to dismantle the structure of the Arabic word, examining the distinctive functions of the phoneme (positively and negatively) through mechanisms of phonetic substitution and metathesis, alongside the morphological and syntactic functions of the morpheme. The research concludes that the phoneme and morpheme constitute the essential driving force for producing meaning, and that the bond between them is organic and inseparable, reflecting the ingenuity of the Arabic linguistic organization and its rigor in morphological adaptation and expressive economy.
Keywords: Phoneme; Morpheme; Morphophoneme; Semantic Function; Arabic Linguistic System; Linguistic Analysis